Systems Design for Remote Healthcare - Maharatna, Koushik; Bonfiglio, Silvio (Springer New York : Imprint: Springer, 2014)
This book provides a multidisciplinary overview of the design and implementation of systems for remote patient monitoring and healthcare. Readers are guided step-by-step through the components of such a system and shown how they could be integrated in a coherent framework for deployment in practice. The authors explain planning from subsystem design to complete integration and deployment, given particular application constraints. Readers will benefit from descriptions of the clinical requirements underpinning the entire application scenario, physiological parameter sensing techniques, information processing approaches and overall, application dependent system integration. Each chapter ends with a discussion of practical design challenges and two case studies are included to provide practical examples and design methods for two remote healthcare systems with different needs. ·         Provides a multi-disciplinary overview of next-generation mobile healthcare system design; ·         Includes fundamental knowledge from clinical science, computer science, electronics, and communication technology to give a complete overview of necessary steps for effective, integrated system design; ·         Discusses practical requirements and illustrates system design with two case studies in remote patient monitoring.